2003
DOI: 10.1248/bpb.26.1730
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Constituents in Plants 2. Xanthones from the Stem Bark of Garcinia subelliptica

Abstract: In the preceding paper in this series, 1) we described the identification of trypanocidal constituents in Guaco (Aristolochia taliscana, Aristolochiaceae) against epimastigotes of the rotozoan Trypanosoma cruzi, which is the etiologic agent of Chagas' disease (American trypanosomiasis). It is transmitted to humans by triatomine bugs or through blood transfusion. In the course of our search for trypanocidal constituents in plants, we have found that the MeOH extract of the stem bark of Garcinia subelliptica MER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…10) MC 100 values of compounds 1-10 against epimastigotes and trypomastigotes were estimated by the same method as mentioned in the previous papers, 2,9) and are summarized in Table 3. Gentian violet 11) and ketoconazole 12) were also tested for comparison.…”
Section: 9)mentioning
confidence: 99%
See 3 more Smart Citations
“…10) MC 100 values of compounds 1-10 against epimastigotes and trypomastigotes were estimated by the same method as mentioned in the previous papers, 2,9) and are summarized in Table 3. Gentian violet 11) and ketoconazole 12) were also tested for comparison.…”
Section: 9)mentioning
confidence: 99%
“…2,9) Assay of Trypanocidal Activity The activity was expressed as the MC 100 value (mg/ml or mM), which was defined as the minimum concentration at which all the epimastigotes or trypomastigotes become immobilized after 24 h incubation. 10) MC 100 values of compounds 1-10 against epimastigotes and trypomastigotes were estimated by the same method as mentioned in the previous papers, 2,9) and are summarized in Table 3. Gentian violet 11) and ketoconazole 12) were also tested for comparison.…”
Section: Cultivation Of T Cruzimentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds isolated from Garcinia subelliptica (Guttiferae) displayed trypanocidal activity against trypomastigotes and epimastigotes of T. cruzi 47 . Although in this mentioned study fukugetin showed no activity in vivo, our results demonstrated fukugetin was a potent inhibitor of cruzain and parasites extracts with concentrations in nonetheless in the low micromolar range.…”
Section: Discussionmentioning
confidence: 99%